DDEL-02. LUMBAR OMMAYA RESERVOIR- A COST EFFECTIVE ALTERNATIVE TO INTRAVENTRICULAR OMMAYA RESERVOIR FOR TREATMENT OF LEPTOMENINGEAL DISEASE. (14th November 2022) - Peo, Ivo; Kumar, Jay; Krafft, Paul; Tran, Nam
Abstract: Introduction: Lumbar puncture (LP) is a well-established approach for intrathecal (IT) delivery of chemotherapeutics for leptomeningeal disease (LMD). Intraventricular Ommaya reservoir (OR) has supplanted LPs as an easier and safer route for IT administration. Radiotherapy for treatment of LMD must be delayed in order for surgical wound healing following OR placement. Furthermore, prior cranial radiation can thin the scalp, predisposing to wound breakdown. Placement of lumbar Ommaya reservoir (LOR) provides an alternative to IT delivery, but this has not reached a wide-spread acceptance. Objective Provide cost-analysis and report patient outcomes after placement of LOR. METHODS: Following IRB approval, all patients undergoing LOR placement between 2018 and 2020 were retrospectively reviewed. Patients age, primary tumor, survival lengths and complications were reviewed. Average procedure-related treatment cost was obtained from an uncomplicated representative case excluding the surgeon's fee. RESULTS: Fourteen patients (mean age 46.35 years) were identified. The mean follow-up was 440.7 (25-1003) days post-surgery. Acute lymphoblastic leukemia (n = 4), acute myeloblastic leukemia (n = 3), breast carcinoma (n = 3), ependymoma (n = 3), lymphoma (n = 2) and lung adenocarcinoma (n = 1) were identified as underlying malignancy. LMD was diagnosed on average after 581.1 days after the diagnosis of the underlying malignancy. 8 patients succumbed to their malignancy on average after 463.9 and 314.6 days after the diagnosis of LMD and LOR surgery, respectively. There were 2 complications – pain at the site of the LOR and a fractured catheter caused by inadvertent puncture of the catheter. No infections or wound healing complications were noted. Typical cost for placement of LOR and OR was – 17, 350 USD and 29, 052 USD, respectively. Placement of the LOR proved to be more cost-effective in this cohort by approximately 40% cost reduction. CONCLUSION: Placement of LOR is a cost effective alternative to cranial OR with low complication profile, and well tolerated by patients.